The Role of Digitalization in the Internationalization of MSMEs in Malang Regency: A Case Study of Coffee Business in Dampit - Eko Juni Wahyudi; Sudarmiatin; Puji Handayati (International Journal of Business and Quality Research, 2025)
This study aims to analyze the role of digitalization in supporting the internationalization of Micro, Small, and Medium Enterprises (MSMEs) in Kabupaten Malang, especially in coffee businesses in the Dampit area. In the era of globalization and digitalization, MSMEs have increasingly opportunities to expand their markets to the international level by utilizing digital technology. This study uses a qualitative approach with a case study method to explore the experiences and challenges faced by coffee entrepreneurs in Dampit who have adopted digital technology in running their businesses. The results of the study show that digitalization, through social media and e-commerce platforms, provides easy access to global markets, increases product exposure, and opens up new opportunities for Dampit coffee entrepreneurs to introduce their products abroad. However, obstacles related to understanding technology and export regulations are challenges that must be overcome